2017
DOI: 10.1186/s40623-017-0674-7
|View full text |Cite
|
Sign up to set email alerts
|

Variations in seismic velocity distribution along the Ryukyu (Nansei-Shoto) Trench subduction zone at the northwestern end of the Philippine Sea plate

Abstract: The Ryukyu (Nansei-Shoto) island arc-trench system, southwest of Japan, is formed by the subduction of the Philippine Sea (PHS) plate. Among the subduction zones surrounding the Japan Islands, the Ryukyu arc-trench system is unique in that its backarc basin, the Okinawa Trough, is the area with current extensively active rifting. The length of the trench is around 1400 km, and the geological and geophysical characteristics vary significantly along the trench axis. We conducted multichannel seismic (MCS) reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 33 publications
2
31
0
3
Order By: Relevance
“…The spatial extent of this thick low‐ V p area is about 30 km in the trench‐parallel direction, and we observed no other comparable layers in other eastern and western profiles. Nishizawa et al () reported that the crust of the subducting PHS has a considerable variation in both thickness and velocity structure along the entire Ryukyu Trench subduction zone. Since there are many seamounts with spatial extents similar to this convex structure on the incoming PHS, it is possible that this thick crust corresponds to a subducted seamount or topographic high (gray circle in Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial extent of this thick low‐ V p area is about 30 km in the trench‐parallel direction, and we observed no other comparable layers in other eastern and western profiles. Nishizawa et al () reported that the crust of the subducting PHS has a considerable variation in both thickness and velocity structure along the entire Ryukyu Trench subduction zone. Since there are many seamounts with spatial extents similar to this convex structure on the incoming PHS, it is possible that this thick crust corresponds to a subducted seamount or topographic high (gray circle in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the outer rise is not developed along the Ryukyu Trench based on the seafloor topography. In reality, there are no seismic refraction images showing the occurrence of hydration (i.e., velocity reduction in the slab crust and mantle) seaward of the trench axis along the Ryukyu Trench (Nishizawa et al, ). Therefore, we should consider other causes of slab mantle hydration in this study area, such as the magmatic effects of plumes (Seno & Yamanaka, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Müller and Landgrebe () reported a strong correlation between subducting fracture zones and areas of megathrust earthquake resulting from strong interplate coupling. A zonal high free‐air gravity anomaly is recognized between 125°E and 129°E along the forearc of the Nansei‐Shoto Trench (Hsu et al, ; Nishizawa et al, ; Sandwell et al, ). The gravity high is associated with the mound‐like submarine topography, which may be due to compressional deformation through the subduction of the stacked oceanic plate (Hsu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…1). Early and recent active-source seismic surveys confirmed that despite having been stretched through the rifting process, the Ryukyu arc exhibits structural characteristics of typical continental lithospheres, such as thick felsic upper crust with P wave velocities of ~ 6.0 km/s, ensuring that the Ryukyu arc still preserves original continental materials and is thus essentially characterized as a continental arc (Murauchi et al 1968;Iwasaki et al 1990;Arai et al 2016Arai et al , 2017aNishizawa et al 2017) (Fig. 1c).…”
Section: Introductionmentioning
confidence: 95%
“…Another geochemical study shows that the current volcanic front has been active since approximately 2 Ma and that the magma production there is enhanced by fluids dehydrated from the subducting slab (Shinjo et al 2000). On the contrary to these advances, internal architectures of the volcanic arc based on geophysical approaches are poorly documented: Multiple seismic surveys have been carried out in the study area (Nash 1979;Iwasaki et al 1990;Nakahigashi et al 2004;Gungor et al 2012;Nishizawa et al 2017), but unfortunately none of them have discussed the volcanic structure in detail.…”
Section: Geological Backgroundmentioning
confidence: 99%